CNR e Protezione Civile verso un know-how condiviso - Bernardini, Fulvio (GEOmedia, 2010)
CNR and Civil Protection towards a shared know-how The Italian National Council of Researchers (CNR) and the Civil Protection Department have a central role in preventing and managing natural disasters and emergencies. However, this union is not considered at a national level: this happens because of the different point of views that characterize these two figures. CNR is more focused on a scientifical approach while CPD is more interested on the practical issues of calamities. The workshop which this report refers to has been aimed to solve this 'opposition'.